Person. Fundamental category and Practical Daring - Saldarriaga Madrigal, Andrés (Estudios de Filosofía, 2009)
One of the basic concepts of Practical Philosophy is that of person. Without this concept some essential matters of Politics, Ethics, Law and Morality cannot be coherently thought out. The complexity of human existence – which is “summarized” in that a person is never only a subject of law, a citizen or an inheritor of a certain cultural tradition – implies the risk of reductionism, that is, of the explanation of what it means to carry out the life of a person from only one perspective of human existence. After presenting some of the central periods of Prehistory and History of the concept of person, the article offers some elements that could serve to formulate a non-reductionist concept of person in the speci c realm of the Philosophy of Social Justice.